JSON-Based RSS as an Alternative to XML-Based RSS on AJAX-Based Aggregator Websites - Qori Utama, Dody; Firdaus, Yanuar; Sulistiyo Kusumo, Dana (School of Computing, Telkom University, 2024)
The rapid development of Internet technology makes information can be exchanged very quickly. RSS was born as one of the technologies that makes it easy to exchange information on the Internet. With RSS, exchanging news on the Internet is even easier than subscribing to a newspaper. RSS was created by utilizing the XML data format which is easy to exchange. Over time, a new data type called JSON was born. JSON is an alternative to XML. Everything XML can do can be done by JSON. JSON has a promising performance compared to XML because JSON has a smaller size than XML. In this final project, the author tries to create a new technology for sharing information by utilizing the JSON data format. In this final project, the author compares user-made technology with existing technology from three things, namely the speed of information creation, data size and data reading speed. The author compares these three things in the author's final project. In the end, the information sharing technology proposed by the author in this final project finally has advantages over existing technologies. This technology is ultimately worthy of continued development as an alternative to existing technologies.